Intra-gastric balloons – The past, present and future - Lari, Eisa (Ann Med Surg (Lond), 2021)
Obesity is a complex metabolic illness that is interrelated to a plethora of complications that predispose to avoidable morbidity and mortality. The considerable impact of obesity has invited various therapies ranging from lifestyle advice, pharmacotherapy, endoscopic bariatric therapy and ultimately surgery. Intragastric balloons are space-occupying therapies that aim to increase satiety through mechanical and neuroendocrine mechanisms. Their prevalence is owed to their ease of administration and general safety. However, long term data concerning safety and efficacy is scarce when considering the various types of balloons in use. In this review, we discuss the intragastric balloon comprehensively in terms of efficacy, safety, limitations and future direction.